2016
DOI: 10.12776/ams.v22i1.628
|View full text |Cite
|
Sign up to set email alerts
|

Electro Spark Deposition of Tib2 Layers on Ti6al4v Alloy

Abstract: <p class="AMSmaintext">The electro spark deposition (ESD) method was used to create hard wear resistant layers of TiB<sub>2</sub> ceramic onto Ti6Al4V titanium alloy. Various deposition parameters and ways and condition of deposition were employed in this study. It was showed that the TiB<sub>2</sub> layer on Ti6Al4Vcan be successfully created even using hand operating ESD equipment. Then, the microstructures of the obtained layers TiB<sub>2</sub> layer on Ti6Al4Vwere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Of these methods, the lightest, cheapest, most affordable and most versatile is electrical spark deposition (ESD). The method has a number of advantages over the above methods [11][12][13][14][15][16][17], the main of which are: its simplicity, low cost of equipment, its easy technology, the insignificant heating of the layered products, absence of thermal deformations, low energy consumption and ease of RESEARCH implementation of the technological operations, the possibility of hardening surfaces of complex shapes. The main disadvantages of this method is a small thickness, relatively higher roughness and unevenness of the applied coatings, and lower productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Of these methods, the lightest, cheapest, most affordable and most versatile is electrical spark deposition (ESD). The method has a number of advantages over the above methods [11][12][13][14][15][16][17], the main of which are: its simplicity, low cost of equipment, its easy technology, the insignificant heating of the layered products, absence of thermal deformations, low energy consumption and ease of RESEARCH implementation of the technological operations, the possibility of hardening surfaces of complex shapes. The main disadvantages of this method is a small thickness, relatively higher roughness and unevenness of the applied coatings, and lower productivity.…”
Section: Introductionmentioning
confidence: 99%
“…of Ti6Al4V substrate with TiB 2 by ESD method and EDX microanalysis showed that coating hardness increased due to the formation of precipitated alumina, TiB 2 , and other more complex phases during the ESD process [2] . The TiC-TiB 2 composite coating electrode was used for coating with electro spark deposition method on the surface of 40Cr steel, and the results showed that the main phases of the composite coating were TiB 2 , TiC and For example, while the wear mechanism of 40Cr steel is mainly related to micro shear, the wear mechanism of composite coating emerges as a mixture of micro shear, scratch and fatigue wear [4,6] .…”
Section: Kovacik Et Al Was Successfully Completed Coatingmentioning
confidence: 99%
“…Engineers need coatings to be more resistant to heat, abrasion and corrosion than the working area. To meet these conditions, the chemical and physical properties of the desired conditions on the surface of the material are provided through various technological processes [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…A significant advantage is that due to the diffusion of electrode material into the substrate and vice versa relatively good bonding between the layer and the substrate occurs. ESD method enables to use titanium and titanium alloys (thanks to increase of their surface hardness and wear resistance) as sonotrode cutting tools [10] and also for biomedical applications in tooth impacts [11]. In this paper, the wear properties of TiB 2 and TiB 2 -Ti composites with 15 and 20 % Ti, under various applied loads are presented.…”
Section: Introductionmentioning
confidence: 99%